Communities and Testing for Covid-19 - Steven Stillman; Mirco Tonin (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Between November 18th and 25th, 2020, 348,810 out of 500,607 (69.7 percent) eligible residents of the South Tyrol region of Italy volunteered to take a Covid-19 rapid antigen test. We examine the community characteristics that are associated with higher testing rates. Our findings point to a number of key community determinants of people's willingness to volunteer. Convenience was an important factor. Beyond that, socioeconomic status and religiosity were also both positively related to greater testing.
Keywords: I12; I18; 330; Covid-19; testing; volunteer; religion